2013
DOI: 10.1016/j.immuni.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The Kinase PKCα Selectively Upregulates Interleukin-17A during Th17 Cell Immune Responses

Abstract: SummaryTransforming growth-factor β (TGFβ) has been implicated in T helper 17 (Th17) cell biology and in triggering expression of interleukin-17A (IL-17A), which is a key Th17 cell cytokine. Deregulated TGFβ receptor (TGFβR) signaling has been implicated in Th17-cell-mediated autoimmune pathogenesis. Nevertheless, the full molecular mechanisms involved in the activation of the TGFβR pathway in driving IL-17A expression remain unknown. Here, we identified protein kinase C α (PKCα) as a signaling intermediate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 63 publications
(84 reference statements)
0
30
0
Order By: Relevance
“…In fact, IL-2 has been shown to promote clonal expansion and effector development of T cells in vivo and has been the growth-supporting cytokine in classical T cell clone-transferred EAE studies (63)(64)(65). Within Th17 cells, downregulation of IL-2 expression by TGF-β occurs by a SMAD-mediated inhibition of gene transcription (20)(21)(22)(23). We found that during Th17 differentiation, miR-21 plays a significant role in the downregulation of IL-2 expression and that the antibody against IL-2 abrogated the observed defect in Th17 differentiation induced by Mir21 -/-T cells.…”
Section: Silencing Mir-21 Ameliorates the Clinical Severity Of Eaementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, IL-2 has been shown to promote clonal expansion and effector development of T cells in vivo and has been the growth-supporting cytokine in classical T cell clone-transferred EAE studies (63)(64)(65). Within Th17 cells, downregulation of IL-2 expression by TGF-β occurs by a SMAD-mediated inhibition of gene transcription (20)(21)(22)(23). We found that during Th17 differentiation, miR-21 plays a significant role in the downregulation of IL-2 expression and that the antibody against IL-2 abrogated the observed defect in Th17 differentiation induced by Mir21 -/-T cells.…”
Section: Silencing Mir-21 Ameliorates the Clinical Severity Of Eaementioning
confidence: 99%
“…TGF-β signals are transduced through activation of the SMAD proteins SMAD-2 and SMAD-3 (18), and enhanced generation of Th17 cells is associated with increased TGF-β-induced SMAD-2/3 activation (19)(20)(21). In addition, TGF-β signaling has been shown to downregulate IL-2 expression and abrogate IL-2-mediated suppression of Th17 differentiation (20)(21)(22)(23). However, the role that microRNAs (miRNAs) play in the activation of TGF-βR signaling in driving Th17 cell development and, consequently, Th17-mediated autoimmunity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of PKCα has been reported to selectively inhibit the effector function of Th17 cells at the transcriptional level of IL-17A. Additionally, PKCα has been identified as a critical member of TGFβRI signalling pathway [23]. Thus, isoforms of PKC in T cells are important therapeutic targets for autoimmune pathologies and transplantation [24].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Baier and colleagues [15] showed that the expression of PKCα was up-regulated in murine CD4 + T-cells differentiated into the effector Th17 lineage in vitro. Baier and colleagues [15] showed that the expression of PKCα was up-regulated in murine CD4 + T-cells differentiated into the effector Th17 lineage in vitro.…”
Section: Conventional Pkcsmentioning
confidence: 99%